OPTIMIZING DIGITALIZATION AGRIBUSINESS MSMES: SOAR-QSPM, ISLAMIC ECONOMICS, HEXAHELIX AT RUMAH JAMUR SADAM - Raihana Azzahra; Syahbudi, Muhammad; Rahma, Tri Inda Fadhila (Journal of Sharia Economics, 2026)
This study aims to formulate and determine the priority strategies for optimizing the digitalization of micro-scale agribusiness MSMEs based on Islamic economic values through the hexahelix approach. This study uses a qualitative approach with a case study design, which focuses on an in-depth understanding of the conditions, potential, and challenges of digitalization of the Saddam Medan Mushroom House MSME. Data collection was conducted through in-depth interviews, observations, and questionnaires with key actors in the hexahelix approach. Strategy analysis was performed using the SOAR approach, which was then systematically prioritized through the Quantitative Strategic Planning Matrix (QSPM) as a strategic decision-making tool based on expert assessment. The results of the study show the dominance of the Opportunity and Aspiration dimensions, so that the digitalization development strategy is directed at strengthening Opportunity-Aspiration (OA). The priority strategy focuses on increasing the competitiveness of MSMEs through expanding market reach and strengthening sustainable digital marketing networks in line with Islamic economic principles.